Cloning and sequence analysis of P38 gene of Grapevine fanleaf virus Hangzhou isolated - LI Hong-ye; CHEN Li-geng; ZHOU Xue-ping (浙江大学学报. 农业与生命科学版)
To confirm the characteristics and function of P38 in the viral particles movement, the cDNA fragment of P38 gene of Hangzhou isolate of Grapevine fanleaf virus (GFLV-H) was amplified by RT-PCR with specific primers to the RNA2 sequence of GFLV-F13 and was then inserted into pGEM-T-easy vector. The result of sequence analysis indicated that this gene contained 1044 nucleotides encoding 347 amino acids and were 90% and 96% identical to GFLV-F13 at nucleotide and amino acid level, respectively. Multiple sequence alignment of amino acid sequence showed that homology between P38 gene of GFLV-H and that of Arabis mosaic virus (ArMV) and that of Tomato ringspot virus(TomRSV) was 85% and 38.6%, respectively, while its homology with Tabacco black ring virus(TBLV), Grapevine chrome mosaic virus (GCMV) and Raspberry ringspot virus (RRSV) was below 30%.